2017
DOI: 10.1111/pce.13012
|View full text |Cite
|
Sign up to set email alerts
|

Silencing OsSLR1 enhances the resistance of rice to the brown planthopper Nilaparvata lugens

Abstract: DELLA proteins, negative regulators of the gibberellin (GA) pathway, play important roles in plant growth, development and pathogen resistance by regulating multiple phytohormone signals. Yet, whether and how they regulate plant herbivore resistance remain unknown. We found that the expression of the rice DELLA gene OsSLR1 was down-regulated by an infestation of female adults of the brown planthopper (BPH) Nilaparvata lugens. On one hand, OsSLR1 positively regulated BPH-induced levels of two mitogen-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
(111 reference statements)
2
35
0
Order By: Relevance
“…Previous studies have shown that GA signaling is involved in plant defense [ 7 , 24 ]; therefore, we examined whether the overexpression of OsGID1 affects the resistance of rice to BPH. In a two-choice experiment, gravid BPH females preferred to feed and lay eggs on WT plants than on oe-GID1 plants ( Figure 3 a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that GA signaling is involved in plant defense [ 7 , 24 ]; therefore, we examined whether the overexpression of OsGID1 affects the resistance of rice to BPH. In a two-choice experiment, gravid BPH females preferred to feed and lay eggs on WT plants than on oe-GID1 plants ( Figure 3 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…In rice, the GA-mediated pathway has been found to positively regulate resistance to the brown planthopper (BPH) Nilaparvata lugens (Stål) [ 23 ]. Moreover, Zhang et al [ 24 ] reported that silencing the DELLA gene OsSLR1 enhances the resistance of rice to BPH in the laboratory and field by impairing JA and ethylene pathways, and by enhancing the levels of lignin. These new findings shed light on the role of GA-mediated signaling in plant defenses against herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…The rice DELLA protein OsSLR1, which negatively regulates the GA pathway, also negatively regulates plant resistance to BPH. Silencing of OsSLR1 probably leading to decrease JA, and ET-mediated defense (Zhang et al 2017). The OsGID1-mediated GA pathway positively regulates BPH resistance in rice.…”
Section: Resistance-associated Signal Transduction In Ricementioning
confidence: 97%
“…DELLA proteins, which negatively regulate the gibberellin pathway, have pivotal roles in rice resistance to BPH. Silencing the rice DELLA gene OsSLR1 enhances rice resistance to BPH both in the laboratory and in the field . When infested by gravid BPH adults, rice plants activate the gibberellin/OsSLR1 pathway by decreasing the expression of OsSLR1 , which then enhances rice resistance to BPH by probably decreasing jasmonate‐ and ethylene‐mediated defense, and by activating the gibberellin/OsSLR1‐mediated growth‐related defenses such as lignin production .…”
Section: Molecular Players Of Rice Originmentioning
confidence: 99%